Microsoft excel-assisted project-based learning for students’ mathematical representation: A classroom action research on data presentation - Erna Sari Agusta; Desy Setyaningsih (International Journal of Mathematics and Sciences Education, 2026)
Mathematical representation ability—the capacity to express mathematical ideas through tables, diagrams, symbols, and verbal explanations—is a key competency in mathematics learning. However, Indonesian junior secondary students continue to experience difficulties, particularly in data presentation. This study investigated the effectiveness of Microsoft Excel-assisted Project-Based Learning (PjBL) in improving the mathematical representation ability of 31 seventh-grade students at Madrasah Tsanawiyah Negeri 28 Jakarta, Indonesia. A Classroom Action Research design was conducted in two cycles, each involving planning, action, observation, and reflection. Data were collected through representation-ability tests, classroom observations, semi-structured interviews, and documentation, and analysed using the Miles and Huberman interactive model with source triangulation. Results showed that the mean representation score increased from 65.16 in Cycle I to 78.39 in Cycle II, while the proportion of students achieving the minimum mastery criterion rose from 48.39% to 87.09%. Improvements occurred across all six representation indicators, including presenting data in tables, constructing diagrams, interpreting representations, explaining data, comparing forms of data presentation, and selecting appropriate representations. These findings suggest that integrating PjBL with Microsoft Excel promotes active, contextual, and technology-supported learning that strengthens students’ mathematical representation ability. However, because the study involved a single class of 31 students, the findings represent classroom-specific evidence and should not be statistically generalised to broader student populations.